DONOR CHARACTERISTICS AS RISK FACTORS IN RECIPIENTS AFTER TRANSPLANTATION OF BONE MARROW FROM UNRELATED DONORS: THE EFFECT OF DONOR AGE - Dr. Pawan Kumar; Dr. Swaraj Kumar Sharma; Dr. Garima Singh; Dr. Manoj Kumar Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
INTRODUCTIONUtilizing marrow from unrelated volunteer donors is an established method of treatment for individuals requiring an allogeneic stem cell transplant but lacking a sibling donor with matching HLA. The aim of present study is to “assess the donor characteristics as risk factors in recipients after transplantation of bone marrow from unrelated donors & to report associations between outcome & donor age”.MATERIAL & METHODSThe present retrospective study was conducted at a tertiary care centre among patients who required bone marrow transplantation during the duration of study (2 years). Through convenient sampling a total 100 patients who underwent bone marrow transplantation from an unrelated donor were selected on the basis of inclusion & exclusion criteria. The evaluation addressed possible effects of cytomegalovirus serologic status, donor age, sex & ABO compatibility on overall & disease free survival.RESULTSThe recipient characteristics according to age with respect to gender, mean age, mean time, diseases, CMMV status, match status & GVHD prophylaxis was tabulated. Age was the only donor trait significantly associated with overall & disease-free survival. All the patient of transplantation survived (100) whereas those who survived disease free were 90. Only the age & HLA matching of the donors were shown to be substantially linked with overall or disease-free survival (P < .0001).CONCLUSIONUtilizing younger donors has the potential to decrease the occurrence of illness & enhance the likelihood of survival following bone marrow transplantation. Age should be taken into account when choosing from a pool of volunteer donors that have similar HLA compatibility.